2007
DOI: 10.1038/sj.leu.2404705
|View full text |Cite
|
Sign up to set email alerts
|

The notch pathway positively regulates programmed cell death during erythroid differentiation

Abstract: Programmed cell death plays an important role in erythropoiesis under physiological and pathological conditions. In this study, we show that the Notch/RBPjj signaling pathway induces erythroid apoptosis in different hematopoietic tissues, including yolk sac and bone marrow as well as in murine erythroleukemia cells. In RBPjj À/À yolk sacs, erythroid cells have a decreased rate of cell death that results in increased number of Ter119 þ cells. A similar effect is observed when Notch activity is abrogated by incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 49 publications
5
48
0
Order By: Relevance
“…Around E9, several types of myeloid and erythroid progenitors are detected in both the embryo and the yolk sac, and it is also around this time that the first stem cell activity is detected in the embryo and yolk sac by transplantation of busulphan-conditioned new-born mice (Yoder et al, 1997). Interestingly, only this second wave of definitive hematopoiesis is abrogated in the Notch mutant embryos, including Notch1, RBPjκ/CSL or Jagged1 knockouts and the stem cell activity is completely lost in the Notch1 mutant embryos Robert-Moreno et al, 2007;Robert-Moreno et al, 2008). Together this data supports the idea that there are two well-differentiated genetic programs responsible for embryonic hematopoiesis, being one Notch-dependent and the other Notchindependent.…”
Section: Notch Mutant Phenotypes In Embryonic Hematopoiesis: the Yolksupporting
confidence: 59%
See 1 more Smart Citation
“…Around E9, several types of myeloid and erythroid progenitors are detected in both the embryo and the yolk sac, and it is also around this time that the first stem cell activity is detected in the embryo and yolk sac by transplantation of busulphan-conditioned new-born mice (Yoder et al, 1997). Interestingly, only this second wave of definitive hematopoiesis is abrogated in the Notch mutant embryos, including Notch1, RBPjκ/CSL or Jagged1 knockouts and the stem cell activity is completely lost in the Notch1 mutant embryos Robert-Moreno et al, 2007;Robert-Moreno et al, 2008). Together this data supports the idea that there are two well-differentiated genetic programs responsible for embryonic hematopoiesis, being one Notch-dependent and the other Notchindependent.…”
Section: Notch Mutant Phenotypes In Embryonic Hematopoiesis: the Yolksupporting
confidence: 59%
“…As previously mentioned, pre-and post-circulation hematopoiesis in the yolk sac of RBPjκ/CSL null embryos is apparently normal (Robert-Moreno et al, 2007). Nevertheless, when we analyzed the erythroid Ter119 + cells in the blood islands of the RBPjκ null yolk sacs, we found an increase in the percentage and number of these cells that was attributed to reduced apoptosis.…”
Section: Notch Signaling Modulates Red Cell Homeostasis In the Yolk Sacmentioning
confidence: 48%
“…Notch in myeloid/erythroid differentiation It has been shown that Notch1/RBP-J positively regulates apoptosis during erythroid development [146]. However, its role in myelopoiesis remains unclear and controversial.…”
Section: Notch and B-cell Developmentmentioning
confidence: 99%
“…[22][23][24][25] Targeted inactivation of the Notch signaling components Notch1, RPBJk, Jag1 and Mib1 showed that Notch is essential for definitive hematopoiesis in the intraembryonic P-Sp/AGM region. 26,27 The tyrosine kinase receptor-2 (Tie2) is expressed on vascular endothelium and on HSCs, and Tie2 þ cells contain hemangioblasts able to differentiate into hematopoietic and endothelial lineages. 28 Since both Tie2 and Notch1 intracellular domain (N1ICD) proteins have similar expression patterns very early in the YS blood island, 29,30 we have used the Tie2-Cre driver line 31 to overexpress Notch1 (N1ICD-EGFP (enhanced green fluorescence protein)).…”
mentioning
confidence: 99%